Stories of the Pure Heart: A Narrative Approach to Integrating Sufism into Integrity and Anti-Corruption Learning Designs - Akhmad Hasan Saleh; Trisnawati Trisnawati; Krim Ulwi (Yayasan Adra Karima Hubbi, 2026)
Background. Corruption remains a persistent challenge in public governance, undermining institutional integrity, social justice, and public trust. Existing anti-corruption policy evaluations mainly emphasize legal compliance and administrative control, while often neglecting the moral and spiritual dimensions that shape individual behavior. This study introduces a Sufi-based perspective by integrating tazkiyat al-nafs (self-purification) into anti-corruption policy evaluation, an element largely absent from conventional evaluation models. Purpose. This study aims to develop a Sufi-based conceptual framework for evaluating anti-corruption policy by integrating spiritual ethics with integrity education. Method. This research employs a qualitative approach using library research. The literature selection criteria include: (1) classical and contemporary Sufi texts explicitly discussing self-ethics; (2) public policy and anti-corruption evaluation literature from the last two decades; and (3) value-based integrity education studies. Thematic analysis was conducted by examining relationships among key Sufi concepts (tazkiyat al-nafs, ihsan, muraqabah, akhlaq al-karimah) and linking them to policy evaluation indicators such as compliance, effectiveness, and behavioral sustainability. Results. The findings show that integrating Sufi spiritual ethics into integrity education provides a more holistic framework for evaluating anti-corruption policies. The proposed framework can be operationalized through three levels of evaluation: (1) process indicators, including the frequency of muraqabah-based ethical reflection in staff development programs; (2) output indicators, reflected in improvements in akhlaq al-karimah within performance assessments; and (3) impact indicators, measured through reductions in integrity violations associated with weak spiritual self-awareness. This approach extends conventional evaluation beyond institutional effectiveness and regulatory compliance by emphasizing ethical awareness, character formation, and moral transformation. Conclusion. The study proposes a Sufi-based evaluation framework that bridges procedural and spiritual dimensions in anti-corruption policy. The framework offers both theoretical and practical contributions by integrating spiritual-ethical indicators into policy evaluation and integrity development programs, particularly within governance systems in Muslim-majority societies.